KONSERVASI LENGAS TANAH MELALUI REKAYASA LINGKUNGAN PADA LAHAN PASIR BERIRIGASI TEKNIS DI PANTAI BUGEL KABUPATEN KULON PROGO - Sudaryono, Sudaryono (Jurnal Teknologi Lingkungan, 2005)
By more decreasing supply of the fertility agriculture land, hence to optimize the usage of marginal land like coastal land is a good way out to improve the farmer income, although demanded to various technological innovation as the environmental engineering form that able to support repairmen of the farming.One step is making conservation of land maoisture and efficiency of the water usage. The result or the technological innovations was treatment with planting system under the shade and combined with mulls, sprinkler irrigation. Now the sprinkler irrigation in the best way on increasing the land moisture rate and then followed by treatment of the shde usage, mulls and drip irrigation, while the worst treatment is without the shade usage both using mulls and drips irrigation